STRATEGI PENGEBANGAN DAYA TARI WISATA AIR TERJUN BABAK PELANGI DESA LANTAN KABUPATEN LOMBOK TENGAH - Abdul Hanan; Primus Gadu; ander sriwi (Journal Of Responsible Tourism, 2023)
This study discusses the strategy of developing a tourist attraction for the rainbow waterfall in Lantan Village, Central Lombok Regency. This research was conducted to answer the problems that became the focus of the research, namely the carrying capacity of the rainbow waterfall to be used as a natural tourist attraction in Lantan Village, Central Lombok Regency. Data collection in this study used the method of observation, interviews and documentation with a qualitative descriptive approach. The results showed that the development model of the rainbow waterfall in Lantan Village is a development location of the rainbow waterfall in Lantan Village. And applied in the form of potential that is owned as a promotional support to be developed and applied in the form of direct participation or the community has directly carried out tourism activities in the Rainbow Waterfall area of ​​Lantan Village by taking the role of subject and object simultaneously, meaning that in the development of the Rainbow Waterfall area Tourism activities in the Rainbow Round Waterfall, the community becomes tourism actors and managers, and at the same time becomes an object that tourists can enjoy through performances of existing attractions.